An overview of advanced instruments for magnetic characterization and measurements - Zhao, Junbiao; Bai, Ligang; Li, Shen; Cao, Zhiqiang; Peng, Yi; Bai, Jinrui; Cai, Xudong; Shi, Xinmin; Lin, Xiaoyang; Wei, Guodong; Zhang, Xueying (Frontiers in Electronics, 2025)
Magnetic materials play a pivotal role in emerging fields such as new energy, information technology, and biomedicine, where accurate magnetic characterization is essential for material innovation and device engineering. Notably, with the burgeoning development of nanomaterials and spintronics, the importance of magnetic characterization has grown significantly, accompanied by increasingly higher requirements for precision and multi-dimensional analysis. This paper elaborates on the working principles and structural components of static magnetic measurement techniques—including Vibrating Sample Magnetometer (VSM), Alternating Gradient Magnetometer (AGM), Magneto-Optical Kerr Effect (MOKE) Microscope, Magnetic Force Microscope (MFM) and Superconducting Quantum Interference Device (SQUID) Magnetometer, as well as dynamic magnetic measurement techniques such as Alternating Current (AC) susceptometry and Ferromagnetic Resonance (FMR). In addition, this review also introduces emerging techniques relevant to spintronics, including Magnetometer based on negatively charged nitrogen-vacancy (NV−) centers in diamond, Spin-polarized Scanning Tunneling Microscope (SP-STM), Lorentz Transmission Electron Microscope (LTEM), and Soft X-ray-based techniques, highlighting their principles and applications in quantum sensing, magnetic imaging, and element-specific spin analysis. This overview emphasizes the unique capabilities and measurement principles of each magnetic characterization instrument, providing users with practical guidance to identify the most appropriate tool based on specific research objectives, material properties, and experimental requirements, thereby improving characterization efficiency and accuracy.